Disintegration and Integration in East-Central Europe 1919 - post-1989 - Loth, Wilfried; Paun, Nicolae (Veröffentlichungen der Historiker-Verbindungsgruppe bei der Europäischen Kommission, 2014)
In this volume, based on a colloquium at the Faculty of European Studies, Babes-Bolyai University, in Cluj-Napoca, the integration of former member states of the Soviet bloc into the European Union is discussed in its broad historical context. 30 scholars are providing a comprehensive insight into the state of integration of East-Central European countries.